Distinct roles of Nb, Ti, and V microalloying elements on the fire resistance of low-Mo steels - Hyungkwon Park; Hyo-Haeng Jo; Seong Hoon Kim; Chiwon Kim; Joonoh Moon; Jun-Ho Chung; Bong Ho Lee; Chang-Hoon Lee (Journal of Materials Research and Technology, 2025)
The high-temperature mechanical stability of structural steels is critical for fire-resistant applications, yet the individual contributions of microalloying elements remain incompletely understood. In this study, we systematically investigated the strengthening mechanisms of three key microalloying elements–Nb, Ti, and V–in low-Mo fire-resistant steel. Each element was independently added to a 0.15Mo-base steel at varying concentrations, and tensile tests were conducted at room temperature (RT) and 600 °C. Microstructural features were characterized in detail using atom probe tomography. Ti enhanced the yield strength (YS) at both temperatures via the formation of (Ti,Mo)(C,N) precipitates, but excessive Ti reduced the YS ratio (σ600oC/σRT) due to solute depletion and precipitate coarsening. V demonstrated minimal precipitation and limited impact at RT, but its linear contribution to high-temperature strength is attributed to secondary hardening by VC. Nb yielded the most consistent strengthening across both temperatures through the combined effects of (Nb,Mo)C precipitation, Nb–C clustering, solid solution strengthening, and bainitic transformation. These findings clarify the element-specific mechanisms governing fire-resistant behavior and suggest that optimized microalloying strategies can enable steels with superior strength retention at elevated temperatures.